(untitled) (TAJ: Journal of Teachers Association, 2009)
This report presents two cases of Lichen Sclerosus et atrophicus. Patients were prepubertal females having itchy white plaques in the vulvar region with on and off burning micturition. No extragenital involvement was seen. Diagnosis was confirmed by histopathology. They were treated with local application of corticosteroid for a variable time period. Both the cases resolved by the age of menarche. These cases are being reported here in the context of its rare occurrence in children and to the best of our knowledge has not yet been reported in children in Bangladesh. The etiopathogenesis, diagnosis and treatment modalities of the disease are reviewed from the literature. doi: 10.3329/taj.v17i1.3490 TAJ 2004; 17(1) : 47-51